Comparison of laying performance and egg quality between peak and late laying phases in Korean quail - Yanfen Ma; Lizhi Lu; Qi Chen; Xuanke Hua; Xinyun Zhang; Xinyu Zhao; Xin Liu (Poultry Science)
The decline in laying performance during the late laying period of poultry causes significant economic losses. This study aimed to investigate the differences in production performance-related parameters between peak (D120) and late (D330) laying phases in Korean quail (Coturnix japonica). A total of 200 D120 quails and 200 D330 quails were randomly divided into 8 groups, with 50 quails per group. The laying rate and egg weight in each group were recorded daily for 8 weeks. At the 8th week, egg quality traits, serum biochemical indices, and the morphology of both ovarian tissue and eggshell gland were evaluated. Compared with D120 quails, the D330 quails exhibited the following changes: (i) Ovarian development deteriorated, with fewer follicles, leading to a reduction in laying rate. (ii) Albumen height, Haugh unit (HU), and eggshell thickness were significantly decreased. Eggshell strength was reduced by 10.05 %, and eggs became more elongated. However, there was no significant differences in egg weight, yolk weight, or yolk color. (iii) The length and density of eggshell gland villi decreased significantly, accompanied by increased lesions, resulting in functional impairment of the eggshell gland. (iv) Serum hormone levels changed significantly: 17β-estradiol (E2), progesterone (P4), and calcitonin (CT) levels decreased, whereas follicle-stimulating hormone (FSH), luteinizing hormone (LH), and parathyroid hormone (PTH) levels increased. (v) Total antioxidant capacity (T-AOC) and the activities of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) decreased significantly in serum, whereas malondialdehyde (MDA) levels increased significantly. (vi) Serum calcium (Ca) levels showed a nonsignificant decreased trend (P = 0.35), whereas serum phosphorus (P) levels increased significantly (P < 0.001). In conclusion, decreased serum E2 and P4 levels, along with reduced antioxidant capacity, contributed to ovarian and eggshell gland deterioration, ultimately impairing laying performance and egg quality in late laying quails.